Anti-Inflammatory Properties of Chemical Probes in Human Whole Blood: Focus on Prostaglandin E2 Production - Bergqvist, Filip; Sundström, Yvonne; Shang, Ming-Mei; Gunnarsson, Iva; Lundberg, Ingrid E.; Sundström, Michael; Jakobsson, Per-Johan; Berg, Louise (Frontiers in Pharmacology, 2020)
We screened 57 chemical probes, high-quality tool compounds, and relevant clinically used drugs to investigate their effect on pro-inflammatory prostaglandin E2 (PGE2) production and interleukin-8 (IL-8) secretion in human whole blood. Freshly drawn blood from healthy volunteers and patients with systemic lupus erythematosus (SLE) or dermatomyositis was incubated with compounds at 0.1 or 1 μM and treated with lipopolysaccharide (LPS, 10 μg/mL) to induce a pro-inflammatory condition. Plasma was collected after 24 hours for lipid profiling using liquid chromatography tandem mass spectrometry (LC-MS/MS) and IL-8 quantification using enzyme-linked immunosorbent assay (ELISA). Each compound was tested in at least four donors at one concentration based on prior knowledge of binding affinities and in vitro activity. Our screening suggested that PD0325901 (MEK-1/2 inhibitor), trametinib (MEK-1/2 inhibitor), and selumetinib (MEK-1 inhibitor) decreased while tofacitinib (JAK inhibitor) increased PGE2 production. These findings were validated by concentration-response experiment in two donors. Moreover, the tested MEK inhibitors decreased thromboxane B2 (TXB2) production and IL-8 secretion. We also investigated the lysophophatidylcholine (LPC) profile in plasma from treated whole blood as these lipids are potentially important mediators in inflammation, and we did not observe any changes in LPC profiles. Collectively, we deployed a semi-high throughput and robust methodology to investigate anti-inflammatory properties of new chemical probes.